(3EOGQI GdLhOI GdTGedI aj YUQ GdGfJQfJs - (3fLe YHhO(B, (3fLes ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3GdeONd Gdi GOGQI GdLhOI GdTGedI , GdMjhO GdSJI , GdGOGhGJ aj GOGQI GdLhOI GdTGedI , LhOI GdNOeGJ , LhOI GdeTQhYGJ , LhOI GdeYQaI , LhOI GddGedehSGJ , GdLhOI GdGdcJQhfjI , LhOI GdHQeLjGJ , GdeONd GdjGHGfj dGOGQI GdLhOI , GdQbGHI GdGMUGFjI Ydi GdLhOI(B.s
(3eQGLY aj cd fgGjI aUds
Keywords: (3GdEOGQIs; (3GdEOGQI(B- (3GdLhOIs; (3GdEjRhs; (3VHW GdLhOIs